Mali - In touch with livestock challenge - International Livestock Research Institute (International Livestock Research Institute, 2021)
This video is one of a series putting farmers' perspectives at the centre of a global discussion. The ‘In Touch with Livestock Challenge’ initiative opens constructive dialogues on sustainable farming in relation to the global goals on climate, biodiversity and food security. On Wednesday 10 November 2021, 13:15 – 14:30 GMT, watch a compilation of farmers' stories from across the world at a COP26 side event 'Towards Sustainable Livestock Systems', organised by the governments of the Netherlands, New Zealand, Colombia and Kenya, the International Livestock Research Institute (ILRI), and Wageningen University and Research (WUR).